2004
DOI: 10.1161/01.atv.0000125704.28058.a2
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle–Dependent Regulation of Smooth Muscle Cell Activation

Abstract: Objective-Although numerous diseases involving cellular proliferation are also associated with phenotypic changes, there has been little direct evidence that cell phenotype and the cell's response to external stimuli are modified during passage through different phases of the cell cycle. In this study, we demonstrate that an association exists between cell cycle progression and the expression of genes involved in cellular activation. VSMCs not only enter cell cycle and proliferate, thereby contributing to neoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 39 publications
2
55
0
1
Order By: Relevance
“…Cell cycle regulatory molecules, such as CDKs and cyclins, are related to the G1 phase of the cell cycle [35][36][37] . In the present study we found that VSMC cell cycle arrest in G0/G1 phase was induced by GA pretreatment; therefore, the effects of GA on expressions of CDK2, CDK4, cyclin E and D1 were further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle regulatory molecules, such as CDKs and cyclins, are related to the G1 phase of the cell cycle [35][36][37] . In the present study we found that VSMC cell cycle arrest in G0/G1 phase was induced by GA pretreatment; therefore, the effects of GA on expressions of CDK2, CDK4, cyclin E and D1 were further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of the expression and function of cell cycle regulatory proteins (including CDKs, cyclins, CKIs, p53, and pRb) provides an important mechanism for growth inhibition (9,10,49,50). The fact that genistein permitted RASMC arrest in G 0 /G 1 phase suggests that modulations of several cell cycle regulatory proteins may occur after genistein treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the cell cycle is regulated by the coordinated action of cyclin-dependent kinases (CDK) in association with their specific regulatory cyclin proteins. Thus, functional activation of CDK-cyclin is required for cell cycle progression (8,9). The kinase activity of these CDK-cyclin complexes is inhibited by two classes of cyclin-dependent kinase inhibitors (CKIs) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Under physiologic conditions, however, the endothelium is not static (3). Pulmonary artery cells are subjected to mechanical forces in the form of cyclic stretch and shear stress resulting from blood pressure and blood flow (4).…”
mentioning
confidence: 99%